IMPLEMENTATION OF MICROLEARNING TECHNOLOGY FOR ECONOMICS STUDENTS THROUGH ONLINE COURSES - Olena Hlazunova; Ralf Schlauderer; Valentyna Korolchuk; Tetiana Voloshyna; Taisia Sayapina; Inna Kostenko; Roman Zolotukha (Інформаційні технології і засоби навчання)
After the outbreak of the pandemic in 2019 and the outbreak of war in the country in 2022, educational institutions at different levels of Ukraine switched to a mixed format of the educational process and were forced to look for modern approaches and technologies for organizing the education of students. This study examines the implementation of microlearning technology using online courses developed on the Moodle platform. Microlearning is a modern learning technology that involves short, intensive training modules focused on the development of specific theoretical knowledge and practical skills. Available online courses, which provide the ability to create and deliver different types of educational content, focus mainly on the formation of necessary knowledge and skills of students, but do not take into account their individual needs and interests in the learning process, and pay little attention to their satisfaction with education in modern conditions. This article investigates the impact of microlearning technology using online courses on students' satisfaction with learning. To determine the level of student satisfaction, an online survey was conducted among 61 students enrolled in the specialty 051 "Economics" programs, which include Business Economics, International Economics, Economic Cybernetics, and Digital Economy, at the National University of Life and Environmental Sciences of Ukraine. All these students were studying using microlearning technology with the use of online courses. As a result, that the level of student satisfaction with learning using this technology is most influenced by such factors as the availability of learning resources, consideration of individual abilities and needs in the online course, opportunities for interaction and communication with the teacher, as well as the format of learning materials and acquired knowledge. Accordingly, these factors should be taken into account when developing online courses and implementing microlearning technologies in the educational process.